Comparative Efficacy and Safety Between Deferiprone and Deferasirox with Special Reference to Serum Ferritin Level and Cardiac Function in Bengali β-Thalassemia Major Children. (3rd September 2021) - Tripathy, Isita; Panja, Amrita; Dolai, Tuphan Kanti; Mallick, Asim Kumar
Abstract: Deferiprone (DFP) and deferasirox (DFX) are the most well-known, efficacious and safe chelators to reduce the serum ferritin (SF) level in multi transfused thalassemic children, although there are few reports available for assessing the efficacy between DFP and DFX. We compared the efficacy of DFP vs. DFX as iron chelating drugs in β-thalassemia major (β-TM) patients. Pediatric patients diagnosed to carry β-TM, aged between 2 and 10 years, were recruited. A suitable data collection form and questionnaire were used. Paired and unpaired t -tests were used to compare the safety and efficacy of the chelating drugs DFP and DFX. The mean SF level at the 12th month was found to be 3016.73 ± 670.04 ng/mL ( p  = 0.002) in the DFX-treated group, which was quite significant in contrast to DFP response, where the value was 3204.06 ± 690.15 ng/mL ( p  = 0.14). There is no statistically significant ( p  = 0.15) difference on relative changes of the left ventricular ejection fraction (LVEF), between these two groups. The adverse effects were transient and none of them required stoppage of therapy. Deferasirox is more effective when compared to DFP in reducing chelating drug-related complications and iron overload specially in multiple transfusion dependent β-TM patients.